Influence of Precracking Techniques on Fracture Toughness of Carbon-Carbon Composites - Sunil Kumar B V (International Journal of Integrated Engineering, 2021)
Carbon-Carbon composites are one such material which give designers significant importance for advanced applications over conventional materials. The remarkable characteristics of carbon-carbon composites had made these products initially extremely useful in the field of aerospace and defense applications. Now, they are presently used in many applications such as biomedical implants, glass, and high temperature glass, etc. In material science, fracture toughness is a trait that depicts the ability of a material to withstand fractures and is one of the most important features in many design applications of any material. A precracked specimen is a sample that is used to accurately assess the distribution of cracks and it is a favored method. This paper describes a comparison of four precracking techniques for carbon-carbon composites using SENB specimen. The potential implications of these techniques on fracture toughness values have been evaluated. The outcome of this work indicates that precracking with a jewel saw is recommended over the other techniques.